Cross-sectional study of smoking exposure: no differential effect on OCT metrics in a cohort of MS patients. Issue 1 (February 2019) - Rosso, Mattia; Kimbrough, Dorlan J; Gonzalez, Cindy T; Glanz, Bonnie I; Healy, Brian C; Rocca, Maria Assunta; Filippi, Massimo; Weiner, Howard; Chitnis, Tanuja
Background: Optical coherence tomography (OCT) provides quantitative measures of retinal layer thickness. Cigarette smoking is a risk factor for multiple sclerosis (MS) onset and disease severity: its effects on OCT metrics have not been assessed. Objective: The objective of this study was to assess the effect of smoking history on retinal nerve fiber layer (RNFL) and ganglion cell-inner plexiform (GCIP) of MS patients by OCT. Methods: 112 MS patients were recruited from the Brigham and Women's Hospital. Spectralis OCT scans were acquired to measure GCIP, peripapillary RNFL, and total macular volume. Multivariable linear mixed effects regression model assessed RNFL and GCIP change with fixed effects for smoking history while adjusting for optic neuritis eye status, age, disease duration, sex, baseline EDSS, and disease modifying therapies (DMTs). Results: Smoking histories were available for 102 patients: 46 (45.10%) had a history of smoking cigarettes and 56 (54.90%) never smoked. No statistically significant differences were found between ever-smokers and never-smokers with respect to GCIP, RNFL, and macular volume. Conclusion: Our study shows no significant difference in retinal thickness between ever-smokers and never-smokers. If confirmed, this result suggests mechanistic differences between the retina and other central nervous system (CNS) compartments in response to smoking and should be noted when considering OCT as a surrogate measure of CNS activity.